The Challenge of Zoom Cloud Meeting in Online Learning Process - Indah Komsiyah (AL-ISHLAH: Jurnal Pendidikan, 2021)
Online learning and teaching are some of the appropriate learning concepts during the current Covid-19 pandemic. This research aims to get in-depth information about the implementation of zoom cloud meetings in the online learning process. This evaluation is carried out to get a solution to the problem while using zoom cloud meeting. The study used a qualitative approach with a survey method. Data were collected through observation, interviews, and questionnaires. The data analysis technique used the stages of reduction, data presentation, data analysis, and concluding. The results showed that the students had difficulties in providing internet networks. Students want each zoom activity to be more interactive and can be varied with other technology applications. In addition, students also need a balance between quota facilities, internet networks, a variety of other learning media, and learning activities that suit student needs. The results of this study have implications for the development of online learning activities according to the ability of students' backgrounds.